The Shifting Paradigm in Maqāsidi Discourse: A Case of Modern Islamic Bioethics - Juhri, Muhammad Alan; Hariani, Hidayah (Lembaga Penelitian dan Pengabdian kepada Masyrakat, 2023)
The advancement of contemporary biomedical issues has brought forth two distinct responses among Muslim scholars. The traditional view, which strictly adheres to the Quran and tradition, tends to find it difficult or even outright rejects modern biomedical practices as they may conflict with religious texts. On the other hand, the rationalist perspective tends to be more open and accommodating towards modern biomedical practices as it relies on independent reasoning detached from revelation. While acknowledging the existence of the traditionalist viewpoint in the modern era, this paper focuses on the rationalist perspective, discussing how biomedical decisions are made. By examining rationalist views on several modern biomedical issues such as organ transplantation, in vitro fertilization, and blood trading, the researcher argues that the flexibility of the maqāsid al-sharīʿah principles has become the framework in the development of this biomedical field. The researcher highlights a shift in the maqāsid paradigm from a theocentric paradigm – interpreting religion with the narrow goal of 'defending God' – to an anthropocentric paradigm – interpreting religion to defend human beings and their rights. Using discourse analysis methodology, this study argues that the paradigm shift towards an anthropocentric maqāsid has integrated Sharia with human subjectivity influenced by interests. Consequently, modern biomedical issues, which address the interests of safeguarding human life, are prioritized. Finally, although such maqāsid may potentially lead to a liquid Islamic law, the researcher concludes that an anthropocentric maqāsid paradigm will be more humane, dynamic, accommodating, and responsive to the demands of human life development. Abstrak: Kemajuan isu-isu biomedis kontemporer saat ini telah memunculkan dua aliran respon yang berbeda di mata para cendekiawan muslim. Pandangan tradisional, yang dengan ketat berpedoman pada Al-Qur’an dan tradisi, cenderung sulit atau bahkan tidak menerima sama sekali praktik-praktik biomedis modern karena bertentangan dengan nash-nash agama. Sementara pandangan rasionalis cenderung lebih terbuka dan akomodatif menerima praktik-praktik biomedis modern karena berpedoman pada penilaian akal sendiri yang terlepas dari wahyu. Terlepas dari mendiskusikan keberadaan pandangan pertama (tradisionalis) di era modern ini, makalah ini akan fokus pada pandangan kedua (rasionalis) dengan mendiskusikan bagaimana putusan-putusan biomedis dikeluarkan. Dengan mengkaji pandangan-pandangan rasionalis terhadap beberapa isu biomedis modern, seperti transplantasi organ, bayi tabung, dan jual beli darah, peneliti berargumen bahwa fleksibilitas prinsip-prinsip maqāsid al-syarīah telah menjadi framework dalam pengembangan bidang biomedis ini. Di sini, peneliti menyoroti adanya pergeseran maqāsid dari paradigma teosentris; menjalankan agama dengan tujuan ‘membela Tuhan’ dalam pengertian yang sempit, ke paradigma antroposentris; menjalankan agama untuk membela manusia dan hak-haknya. Dengan menggunakan metode analisis wacana, penelitian ini berargumen bahwa pergeseran paradigma maqāsid menuju antroposentris telah menjadikan syari’ah menyatu dengan subjektivitas manusia yang dipengaruhi oleh kepentingan-kepentingan. Karenanya, isu-isu biomedis modern, yang menjawab kepentingan menjaga jiwa manusia, adalah diutamakan. Terakhir, meskipun maqāsid seperti ini berpotensi mengarah pada liquid Islamic law, peneliti berkesimpulan bahwa paradigma maqāsid antroposentris akan lebih humanis, dinamis, akomodatif, dan responsif terhadap tuntutan perkembangan kehidupan manusia.